Distribution and abundance of humpback whales, Megaptera novaeangliae, off the coast of Mozambique, 2003 - Findlay, Ken; Meyer, Michael; Elwen, Simon; Kotze, Deon; Johnson, Ryan; Truter, Pieter; Uamasse, Celestino; Sitoe, Samuel; Wilke, Chris; Kerwath, Sven; Swanson, Stephen; Staverees, Linda; et al. (J. Cetacean Res. Manage., 2020)
Humpback whales within the southwestern Indian Ocean undertake annual migrations from summer Antarctic/Southern Ocean feeding grounds to winter breeding grounds in the tropical and sub-tropical coastal waters of Mozambique, Madagascar and the central Mozambique Channel Islands. Little is known of the inter-relationship of humpback whales on each of these wintering grounds, or the inter-relationship of these wintering grounds with the summer Antarctic feeding grounds. A line-transect survey of cetacean species was carried out in Mozambique coastal waters between Cabo Inhaca (26°00’S, 33°05’E) and just north of Mozambique Island (14°26’S, 40°53’E) and between the 20 and 200m isobaths, over the period 26 August to 7 September 2003. The majority (98.1%) of 951.8 n.miles of search effort carried out on this survey was in passing mode due to the high densities of whales encountered. Humpback whales were the only large whales to be identified and the distribution of 691 sightings of an estimated 1,130 individual humpback whales and 132 sightings of an estimated 154 large unidentified whales show distribution throughout the survey region. Two sightings of individual small whales were made in the region of Inhambane. In general, higher than expected sighting densities (based on survey effort) were recorded in the region between Cabo Inhaca and Xai-Xai, and in the region of the Pantaloon and David Shoals to the north east of Quelimane. Lower than expected sighting densities were recorded over the Sofala Banks. No distribution trends could be ascribed to environmental parameters, apart from whales being distributed in waters of higher salinities than expected, possibly due to turbidity associated with low salinity water arising from river input. Groups containing a cow and calf pair were distributed across the entire region surveyed. Analyses of unstratified data result in a total abundance estimate of 6,808 (CV = 0.14) humpback and unidentified whales in the 14,029.5 n.mile2 area surveyed. As a result of the differences in width of the coastal shelf area along the coast of Mozambique, the line transect survey data were further analysed in four strata. Pooling of estimates over these four strata results in a total abundance of 6,664 whales (CV = 0.16), with highest densities in the southernmost stratum and the lowest densities in the narrow shelf region across the Sofala Banks. Similar analyses of humpback whales only resulted in abundance estimates of 5,930 (CV = 0.15) (unstratified data) and 5,965 whales (CV = 0.17) (data analysed by four strata). Although not directly comparable due to differing survey platforms, these estimates indicate the population to have increased since previous surveys in the early 1990s.